Le jardin créole à Fort-de-France : stratégie de résistance face à la pauvreté ? - Jean-Valéry Marc (VertigO, 2011)
In the Caribbean islands about 70 % of the population lives in urban areas today. The crisis of the sugar cane industry in the 1950s was the main factor of the drift from the land of the populations towards the major cities of the Lesser Antilles to find better living conditions there. Constituted mainly of countrymen and occupant often weakly paid jobs, these populations had to adapt at best urban adventures. One of these most visible accommodations lives the Creole garden. It indicates this small spatial unit of agricultural productions, averagely bounded, adjacent to the detached, very wide-spread houses in the rural and urban spaces of Lesser Antilles. It is said « Creole » because characteristic of a farming and cultural mode inherited from precolonial and colonial periods, and centred essentially on the autoconsumption. So, although it collects a wide part of the urban population of the island and the main part of the functions of command, Fort-de-France remains nevertheless marked by a remaining rural life (Marc, 2007 ; Martouzet, 2001). In spite of an IDH placing her, among the main platoon of the Caribbean countries, Martinique accuses strong disparities of standards of living ; an important fringe of her population lives below the poverty line and constantly has to tack between precarious employment, social incomes, and informal work. In the crossing of the heritage, the environment and the autoconsumption, the urban Creole garden reveals a real strategy of economic survival in particular for the least facilitated populations.